Ecosystems and public health - Cárdenas García, Darío (Spei Domus, 2011)
From an environmental and sustainability point of view we must recognize habitat as the essential unit of ecology study in the ecosystem, by definition an area where the relationship between organisms and environment takes place. Ecosystems, e.g. a tropical wet forest –jungle, gallery forests and native savanna and devastation of those natural habitats by pollution, soil sterilization, deforestation and overpopulation have generated a quickly extinction of organisms. We have forgotten that cities depend on natural ecosystem balance, like forests in our planet that represent a big ecosystem where nature balance is preserved because they are a lung for people by catching carbon dioxide and producing oxygen, besides absorbing water rained on Earth, but today due to deforestation they cause a lot of flooding and landslides. So this broken system balance generates disease (vectors) migration from forests to urban areas. The World Health Organization (who) says that increase of new disease, such as the aviary influenza (a threat of pandemic human influenza) could be related to environment devastation.